2010
DOI: 10.3892/ijo_00000829
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 inhibition increases p53 expression and destabilizes MYCN and MYC in neuroblastoma

Abstract: Abstract. Neuroblastoma is a childhood cancer that exhibits either a favorable or an unfavorable phenotype. MYCN and MYC are oncoproteins that play crucial roles in determining the malignancy of unfavorable neuroblastoma. The Hsp90 superchaperone complex assists in the folding and function of a variety of oncogenic client proteins. Inhibition of Hsp90 by small molecule inhibitors leads to the destabilization of these oncogenic proteins and consequently suppresses tumor malignancy. Nonetheless, little is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Inhibition of c-Myc by deguelin in CLL cells shown in this work is an interesting finding in light of its recently described relevance in the metabolic changes that take place in CLL cells upon contact with their tissue microenvironment, changes that promote CLL cell survival and resistance to chemotherapeutic drugs [ 59 ]. This finding is in agreement with already described inhibition of c-Myc by Hsp90 inhibitors [ 60 , 61 ], and could explain the synergy found between deguelin and fludarabine. Postulated mechanisms explaining this synergy between Hsp90 inhibitors and fludarabine include downregulation of antiapoptotic proteins as a consequence of AKT/NFκB inhibition [ 45 ] or downregulation of DNA repair enzymes and checkpoint regulators that limit the capacity of CLL cells to repair fludarabine-induced DNA damage [ 61 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Inhibition of c-Myc by deguelin in CLL cells shown in this work is an interesting finding in light of its recently described relevance in the metabolic changes that take place in CLL cells upon contact with their tissue microenvironment, changes that promote CLL cell survival and resistance to chemotherapeutic drugs [ 59 ]. This finding is in agreement with already described inhibition of c-Myc by Hsp90 inhibitors [ 60 , 61 ], and could explain the synergy found between deguelin and fludarabine. Postulated mechanisms explaining this synergy between Hsp90 inhibitors and fludarabine include downregulation of antiapoptotic proteins as a consequence of AKT/NFκB inhibition [ 45 ] or downregulation of DNA repair enzymes and checkpoint regulators that limit the capacity of CLL cells to repair fludarabine-induced DNA damage [ 61 ].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with already described inhibition of c-Myc by Hsp90 inhibitors [ 60 , 61 ], and could explain the synergy found between deguelin and fludarabine. Postulated mechanisms explaining this synergy between Hsp90 inhibitors and fludarabine include downregulation of antiapoptotic proteins as a consequence of AKT/NFκB inhibition [ 45 ] or downregulation of DNA repair enzymes and checkpoint regulators that limit the capacity of CLL cells to repair fludarabine-induced DNA damage [ 61 ]. According to our results, both AKT/NFκB inhibition and reinforcement of fludarabine-induced DNA damage take place in degluelin plus fludarabine treated CLL cells, and likely cooperate in induction of apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…STIP1 has been reported to be overexpressed in PDAC cell lines and malignant tissue samples from patients with PDAC (27). STIP1 is proposed as a co-chaperone of HSP90 that regulates c-Myc expression in cancerous cells (34). It is reported that c-Myc interacts with an E-box in the hTERT promoter resulting in expression of hTERT and telomerase (35).…”
Section: Discussionmentioning
confidence: 99%
“…The BiFC assay provided evidence that GOLPH3 interacts with STIP1 and heat shock protein group including HSP90 (Figure 1C). As a 60kDa protein that belonging to one of the co-chaperones families, STIP1 reversibly binds to the protein chaperones HSP90, which regulates c-Myc expression in cancerous cells (33,34). c-Myc activates hTERT transcription via E-box binding, resulting in direct regulation of telomerase activity (35).…”
Section: Knockdown Of Golph3 or Stip1 Downregulates Htert/cyclin D1 By C-myc In Pdac Cellsmentioning
confidence: 99%
“…Addition of a BCL-2 inhibitor such as ABT199/venetoclax thus presumably facilitated the commitment of the tumor cells to undergo apoptosis. The efficacy of such drug combinations is further shown by the cleavage of HSP90 and decreased level of c-MYC, two pro-survival proteins ( Figure 2A ) [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%